Peer influences and proenvironmental behavior: Panel evidence for the role of regional prevalence and diversity - Martin Binder; Ann-Kathrin Blankenberg; Heinz Welsch (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
Pro-environmental behavior depends on the behavior of others. For a UK panel data set, we find that individuals' pro-environmental behavior increases in the behavior of peers in their region. This happens the more so, the greener the self-image of an individual. Diversity of regional green behavior plays a further role, with fractionalization negatively related to pro-environmental behavior and polarization positively so: peer pressure exerts a less strong influence when behaviors are diverse, and a stronger influence when behaviors are very polarized.
Keywords: Q53; Q56; 330; pro-environmental behavior; peer influence; prevalence; fractionalization; polarization; UKHLS